Frequency and Types of Pathological Upper Gastrointestinal Endoscopy Findings in Clinically Healthy Individuals - Elisabeth Scheidl; Claus Benz; Peter Loeff; Volker Groneck; Andreas König; Alban Schulte-Fischedick; Hendrik Lück; Uwe Fuhr (Adis, Springer Healthcare, 2020)
Abstract Background and objective Beyond its application for diagnostics in patients, esophagogastroduodenoscopy (EGD) is used to assess gastrointestinal drug effects in clinical trials, where the interpretation of any pathological findings depends on the respective background variability. The objective of this analysis was to characterize the occurrence of pathological findings in the upper gastrointestinal tract in symptom-free healthy individuals. Methods A baseline EGD was performed in clinically healthy individuals in three clinical trials aimed to assess gastrointestinal tolerability of drugs. Pathological findings were described by type (redness, erosion, ulcer or other), number, size and location, and by clinical relevance as assessed by the endoscopist. Characteristics of volunteers were tested as potential covariates. Results A total of 294 EGDs were assessed. Characteristics of individuals were as follows: 257 (87.4%) males, age (mean ± SD) 32.0 ± 8.1 years, body weight 76.0 ± 10.6 kg, body mass index (BMI) 24.0 ± 2.5 kg/m2, 200 consumed alcohol, 250 (of 290 where this information was available) consumed caffeine and 39 (of 152) were smokers, 30 (of 151) tested positive for H. pylori. Any pathological finding was present in 79.6%. Clinically relevant findings occurred in 44.2%, mainly erosions (39.1%). Nine stomach ulcers were observed. Only age and BMI had a statistically significant relationship to overall pathological findings [age 3.4 years higher (p = 0.027), and BMI 1.6 kg/m2 higher (p < 0.001); for clinically relevant vs no findings]. Conclusion Upper gastrointestinal tract mucosal lesions, including those assessed as clinically relevant, are frequent in clinically healthy individuals, impeding the assessment of causality for both disease and drug effects on gastrointestinal health.